The Relevance of Islamic Religiosity, Islamic Work Ethics, and Job Satisfaction of Employees in Islamic Financial Institutions in Gorontalo. - Luqmanul Hakiem Ajuna (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. This research analyses the influence of Islamic religiosity and the Islamic work ethics on job satisfaction of employees in Islamic Financial Institutions in Gorontalo Indonesia. Using a questionnaire method, this research had 137 employees as samples spreading in 14 Islamic financial institutions in Gorontalo Province. This research used multiple linear regression approach. Based on data analysis, the result showed that simultaneously the religiosity and Islamic work ethics variables affected the employee’s job satisfaction, whereas in partial, only the Islamic work ethics variable influenced the job satisfaction. Overall, the employees have not yet found a medium to explore their Islamic potential, thus their expressions of religiosity seemed to be scriptural and only limited to practices and rituals.Keywords : Islamic Religiosity, Islamic Working Ethics, Job Satisfaction Abstrak. Relevansi Religiusitas Islam, Etika Kerja Islam, dan Kepuasan Kerja Pegawai Lembaga Keuangan Syariah di Gorontalo. Penelitian ini melihat pengaruh religiusitas Islam dan etika kerja Islam terhadap kepuasan kerja di lembaga keuangan syariah di Provinsi Gorontalo. Berdasarkan hasil analisis data yang diolah dengan menggunakan metode regresi linier berganda dengan mengambil sampel sebanyak 137 pegawai yang tersebar di 14 lembaga keuangan syariah di Provinsi Gorontalo. Penelitian ini menyebutkan bahwa secara simultan variabel religiusitas dan etika kerja Islam berpengaruh terhadap kepuasan kerja, sedangkan secara parsial hanya variabel etika kerja islam yang memberi pengaruh pada kepuasan kerja. Secara menyeluruh  bahwa pegawai belum memiliki wadah untuk mengeksplor potensi keberagamaan mereka sehinga ekspresi kebebasan keberagamaan masih terkesan kaku dan hanya terbatas pada praktik dan ritualisme semata.Kata Kuci: religiusitas islam, etika kerja Islam, dan kepuasan kerja